2020
DOI: 10.1093/mnras/staa1987
|View full text |Cite
|
Sign up to set email alerts
|

The power of coordinate transformations in dynamical interpretations of Galactic structure

Abstract: Abstract Gaia DR2 has provided an unprecedented wealth of information about the positions and motions of stars in our Galaxy, and has highlighted the degree of disequilibria in the disc. As we collect data over a wider area of the disc it becomes increasingly appealing to start analysing stellar actions and angles, which specifically label orbit space, instead of their current phase space location. Conceptually, while $\bar{x}$ and $\bar{v}$ tell us about the pot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 64 publications
0
29
2
Order By: Relevance
“…In particular, the radial velocity map is almost identical to that based on the entire G3RV2, implying that the stellar density structures in the angular momentum space can not be explained by local stars (or selection/extinction biases). This does not support the possibility discussed in the recent study by Hunt et al (2020), that the overdensities in (X g , Y g ) we found in Khoperskov et al (2020b) are generated by the local v R -v φ moving groups because the G3RV2 sample is dominated by stars in the SNd. Although the large majority of stars in the G3RV2 sample indeed can be found close to the Sun, the distant (D > 1 kpc) stars show very similar patterns in Fig.…”
Section: Mw Spiral Arms In the G3rv2contrasting
confidence: 99%
See 2 more Smart Citations
“…In particular, the radial velocity map is almost identical to that based on the entire G3RV2, implying that the stellar density structures in the angular momentum space can not be explained by local stars (or selection/extinction biases). This does not support the possibility discussed in the recent study by Hunt et al (2020), that the overdensities in (X g , Y g ) we found in Khoperskov et al (2020b) are generated by the local v R -v φ moving groups because the G3RV2 sample is dominated by stars in the SNd. Although the large majority of stars in the G3RV2 sample indeed can be found close to the Sun, the distant (D > 1 kpc) stars show very similar patterns in Fig.…”
Section: Mw Spiral Arms In the G3rv2contrasting
confidence: 99%
“…3 shows that in our high-resolution simulation single guiding space overdensities dominate individual spiral arms. However, this does not rule out the possibility that in other simulations, depending on the dynamical nature of the spiral arms, several such overdensities contribute substantially to a single arm (see, e.g, Hunt et al 2020). In this case, the XY-locus of the guiding space overdensities would overlap, which we have not observed in the available Gaia data (Khoperskov et al 2020b), at least for the most prominent features.…”
Section: N-body Model: Angular Momentum (Guiding) Space Overdensitiesmentioning
confidence: 61%
See 1 more Smart Citation
“…There is more than one feature in the local kinematics that looks like the bar OLR's velocity flip. But only one can be the true OLR (if at all visible) and the others will be related to other bar resonances (e.g., Monari et al 2019a;Hunt & Bovy 2018;Asano et al 2020) and spiral arms (De Simone et al 2004;Chakrabarty 2007;Quillen et al 2018;Michtchenko et al 2018;Hunt et al 2019;Khoperskov et al 2020;Hunt et al 2020). Our angle-based method provides additional constraining evidence.…”
Section: Comparing the Action-and Angle-based Methods For The Olrmentioning
confidence: 94%
“…Four of these structures were suggested to correspond to the Scutum-Centaurus, Sagittarius, Local, and Perseus arms, while the remaining two may be associated with the main resonances of the Milky Way bar and the outer Lindblad resonance beyond the solar circle. While Hunt et al (2020) presented a different point of view. They suggested that the stellar density structures identified by Khoperskov et al (2020) are known kinematic moving groups, rather than a coherent structure in physical space such as spiral arms.…”
Section: Evolved Starsmentioning
confidence: 99%